2006
DOI: 10.1016/s1556-0864(15)31603-8
|View full text |Cite
|
Sign up to set email alerts
|

EGFR Dinucleotide Repeat Polymorphism as a Prognostic Indicator in Non-small Cell Lung Cancer

Abstract: Background:The epidermal growth factor receptor (EGFR) has been implicated in tumor growth and progression. Intron 1 of the EGFR gene contains a polymorphic simple sequence repeat (SSR) of 14 to 21 CA dinucleotides, the length of which correlates inversely with the level of EGFR transcription. The authors hypothesized that a shorter length of tumor SSR would be associated with poorer survival in patients with non-small cell lung cancer (NSCLC). Methods: Patients enrolled in Eastern Cooperative Oncology Group E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 22 publications
(29 reference statements)
3
30
1
Order By: Relevance
“…Potential explanations include a greater prevalence of activating epidermal growth factor receptor (EGFR) mutations in Asians, 32 which generally confer a better prognosis, or the greater prevalence of intraallelic EGFR polymorphisms in Asians, 33 which may confer a survival advantage in patients with NSCLC. 34 This report is retrospective in nature and shares many limitations of other population-based studies, including the lack of central pathology review. We could not ascertain the timeline or sequence of the treatment modality rendered.…”
Section: Discussionmentioning
confidence: 99%
“…Potential explanations include a greater prevalence of activating epidermal growth factor receptor (EGFR) mutations in Asians, 32 which generally confer a better prognosis, or the greater prevalence of intraallelic EGFR polymorphisms in Asians, 33 which may confer a survival advantage in patients with NSCLC. 34 This report is retrospective in nature and shares many limitations of other population-based studies, including the lack of central pathology review. We could not ascertain the timeline or sequence of the treatment modality rendered.…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent studies in Japanese cohorts treated with gefitinib as first-line or adjuvant therapy did not show significant associations [57,58], while lower response rates to gefitinib were observed in Caucasian patients harboring the G/C haplotype [59]. Another EGFR region with relevant polymorphisms is located in the intron-1, characterized by 14 to 21 CA-repeats; with shorter alleles of a CA-dinucleotide repeat polymorphism in intron-1 associated with enhanced EGFR transcription, improved response rates, and longer OS after gefitinib treatment in different ethnicity cohorts [56,[58][59][60][61][62][63][64][65][66][67][68]. Most studies reported a better response to gefitinib, both in Japanese and Caucasian patients.…”
Section: Pharmacogenetics Of Egfr-tkismentioning
confidence: 99%
“…Two Asian studies (Han et al, 2007;Nie et al, 2007) and one American study found associations with lung cancer survival or toxicity with gefitinib, whereas others found no significant association (Ichihara et al, 2007;Gregorc et al, 2008). Shorter CA repeat lengths were associated with poorer survival in the absence of therapy with an EGFR TKI, which is a reversal of expectations in TKI-treated patients (Dubey et al, 2006). The multidrug transporter ABCG2 was shown to be active in removing gefitinib from cells (Elkind et al, 2005).…”
Section: Genetic Polymorphisms and Egfr-targeted Drugsmentioning
confidence: 99%